Design of dashboard progress monitoring of work contract work at PT Lautan Berlian Nusantara - Putra, Hartono Yuppy; Wurijanto, Tutut; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
PT. Lautan Berlian Nusantara is Shipping Marketing in the field of Maintenance, Supplier and as a partner of the Main Command (KOTAMA). Main Command (KOTAMA) is an area divided according to the Indonesian Navy's National Army (TNI AL), the region is the western and eastern regions where the area is divided into the Navy Material Agency (Dismatal) and the Ship Maintenance Agency (Disharkap). PT. Lautan Berlian Nusantara is engaged in construction services and ship engine repair and provides spare parts. PT. Lautan Berlian Nusantara, to get a job first, will auction the parties concerned, after that it will make a contract with the parties concerned. each work contract has some work that must be completed by PT. Lautan Berlian Nusantara, currently from every monitoring and controlling work that is in the work contract is still in the form of recording using Microsoft Excel application. As a result, it causes delays in information, with the delay in information becoming a problem in every process of contract work undertaken. Based on these problems, the solution given will be made monitoring and controlling applications to monitor each process of contract work carried out. The test results show that the application built to support the work contract work process can monitor every process of contract work being carried out. keywords: application, shipping, employment contract.